Review on Crystallization Strategies for Polymer Single Crystals - Tianyu Wu; Jun Xu; Haimu Ye (Crystals, 2024)
Polymer physics has evolved significantly over the past century, transitioning from the early recognition of the chain structure of polymers to a mature field integrating principles from statistical mechanics, thermodynamics, and condensed matter physics. As an important part of polymer physics, polymer single crystals are crucial for understanding molecular structures and behaviors, enhancing material properties, and enabling precise functionalization. They offer insights into polymer crystallization kinetics, serve as templates for nanofabrication, and have applications in electronics, sensors, and biomedical fields. However, due to the complexity of molecular chain movement, the formation of polymer single crystals is still very difficult. Over the decades, numerous researchers have dedicated themselves to unraveling the mysteries of polymer single crystals, yielding substantial findings. This paper focus on the historical evolution and advancements in polymer single crystal research, aiming to offer valuable insights and assistance to fellow researchers in this field.